Xenophon’s Oeconomicus: the “maîtresse de la maison” - Bevilacqua, Fiorenza (Revista Archai, 2021)
Xenophon’s Oeconomicusincludes an interesting treatise on married life, at the hearth of which is the figure of Ischomachus’ wife, such as she is described by Ischomachus’ words to Socrates. It is an almost innovative figure, because she shares the management of the oikosas being responsible for what is carried out within the oikos: her role is different from her husband’s, who runs and manages what is carried out outside of the oikos. Therefore husband’s and wife’s tasks are different, though complementary. The difference in inclinations and, therefore, roles is shown as established by god, nature (as an instrument of god) and custom (nomos). So Ischomachus’ wife is a collaborator and companion of her husband, even though she does not have an equal relation with her him: she manages the activities and people within the oikosaccording to her husband’s directives. Also in the sphere of sexual life she has to conform to his desires and convictions; her own status as a wife will be preserved only if she meets his expectations: paradoxically her own autonomy is other-directed. Even if she may be considered a “maîtresse de la maison”, nevertheless, as Foucault outlined with a very incisive expression, she is anyway the “maîtresse obéissante de la maison”.